Effect of oral environmental pH on the dynamic characterization of bioactive restorative materials - Ong, Joshua Ee Xin; Yap, Adrian U-Jin; Azwatee Abdul Aziz; Noor Azlin Yahya (Penerbit Universiti Kebangsaan Malaysia, 2022)
The objective of this study was to investigate the effects of oral environmental pH on the viscoelastic properties of bioactive restorative materials (BRMs) by using dynamic mechanical analysis. Stainless steel molds were used to fabricate 40 beam-shaped specimens (12 × 2 × 2 mm) for each material. The specimens were finished, measured, randomly divided into four groups (n = 10), and immersed in aqueous solutions of pH 3.0, 5.0, 6.8 and 10.0 at 37 °C for seven days. The specimens were then subjected to dynamic mechanical analysis with a 5 N load and frequency range of 0.1-10.0 Hz. Data were analyzed using one-way ANOVA/Dunnet T3’s test (α = 0.05). Mean elastic modulus spanned from 2.68 ± 0.17 to 6.49 ± 0.71 GPa, while viscous modulus ranged from 0.43 ± 0.03 to 0.62 ± 0.12 GPa. Loss tangent differed from 77.30 ± 4.90 to 164.50 ± 9.12. Significant differences among pH were discerned for (i) Elastic modulus: Cention N - pH 3.0, 5.0, 10.0 > 6.8; Activa Bioactive - pH 3.0, 6.8, 10.0 > 5.0, (ii) Viscous modulus: Cention N - pH 3.0, 5.0, 10.0 > 6.8, and (iii) Loss tangent: Activa Bioactive - pH 5.0 > 3.0, 6.8, 10.0. Significant differences in viscoelastic properties were noted among the BRMs with Activa Bioactive presenting the lowest elastic modulus for all pH. Immersion of all materials in pH 6.8 yielded the highest elastic modulus, except for Activa Bioactive. The effects of environmental pH on viscoelastic properties of BRMs are material-dependent.